A β-N-acetylhexosaminidase Amuc_2109 from Akkermansia muciniphila protects against dextran sulfate sodium-induced colitis in mice by enhancing intestinal barrier and modulating gut microbiota. Issue 4 (8th February 2022) - Qian, Kaiyue; Chen, Shoujun; Wang, Junchao; Sheng, Kangliang; Wang, Yongzhong; Zhang, Min
Abstract : Amuc_2109 protects against colitis by inhibiting the overproduction of pro-inflammatory cytokines, suppressing the activation of colonic inflammatory-signaling pathways, enhancing the intestinal barrier and modulating the gut microbiota. Abstract : Inflammatory bowel disease (IBD) is associated with the microbial composition of the gut and its metabolites. Akkermansia muciniphila is a probiotic that exerts a significant alleviative or therapeutic effect on host enteritis. This study was designed to determine the protective effect and potential mechanism underlying the secretion of β-acetylaminohexosidase (Amuc_2109) by A. muciniphila against dextran sulfate sodium (DSS)-induced colitis in mice. C57BL/6 mice were gavaged with Amuc_2109 for 21 days, and during the last seven days of treatment, they drank DSS dissolved in their drinking water to induce colitis. Our results showed that supplementation with Amuc_2109 improved DSS-induced colitis as evidenced by lowered disease activity index (DAI) scores, reduced weight loss, increased colon length, and inhibited oxidative stress. In addition, Amuc_2109 inhibited the overexpression of inflammatory cytokines (TNF-α, IL-1β, IL-6) and the NLR family pyrin domain containing 3 (NLRP3) inflammasome in DSS-induced colitis. Furthermore, supplementation with Amuc_2109 also restored the mRNA expression of tight junction proteins (ZO-1, occludin, claudin-1). Further analysis of fecal microbial 16S rRNA sequences showed that Amuc_2109 reshaped the intestinal microbiota. While the anti-inflammatory effects of Amuc_2109 were only manifested with the wild-type protein, the anti-inflammatory effects were completely lost after the mutation of its key catalytic amino acids rendered Amuc_2109 inactive. In summary, these findings demonstrate the potential of Amuc_2109, as a therapeutic agent for ulcerative colitis. We posit that it will provide additional assistance in the prevention and treatment of mucus layer-related diseases such as ulcerative colitis.